2013
DOI: 10.1038/msb.2013.35
|View full text |Cite
|
Sign up to set email alerts
|

Insulin/IGF‐1‐mediated longevity is marked by reduced protein metabolism

Abstract: Quantitative proteomics, lifespan analysis, and biochemical assays were utilized to show that Insulin/IGF-1-mediated longevity in C. elegans is strongly associated with a daf-16 dependent global reduction in protein metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
91
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(98 citation statements)
references
References 59 publications
6
91
1
Order By: Relevance
“…The loss of protein homeostasis is one of the hallmarks of aging (Balch et al, 2008;Ló pez-Otín et al, 2013), and protein aggregation is implicated in the pathology of age-related diseases like Parkinson's disease, Huntington's disease, cancer, and Alzheimer's disease (Powers et al, 2009). The idea that loss of protein homeostasis is implicated in aging comes mostly from studies that measure global protein synthesis and translation rates (by 35 S-methionine [ 35 S-Met] incorporation and polysome profiling, respectively) during normal aging and in models of age-related disease (Depuydt et al, 2013Hansen et al, 2007;Kirstein-Miles et al, 2013;Pan et al, 2007;Stout et al, 2013). Other studies used quantitative mass spectrometry or SDS-PAGE and western blotting to measure changes in the relative abundance of proteins in the proteome of aging model systems (Depuydt et al, 2013Kirstein-Miles et al, 2013;Walther et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The loss of protein homeostasis is one of the hallmarks of aging (Balch et al, 2008;Ló pez-Otín et al, 2013), and protein aggregation is implicated in the pathology of age-related diseases like Parkinson's disease, Huntington's disease, cancer, and Alzheimer's disease (Powers et al, 2009). The idea that loss of protein homeostasis is implicated in aging comes mostly from studies that measure global protein synthesis and translation rates (by 35 S-methionine [ 35 S-Met] incorporation and polysome profiling, respectively) during normal aging and in models of age-related disease (Depuydt et al, 2013Hansen et al, 2007;Kirstein-Miles et al, 2013;Pan et al, 2007;Stout et al, 2013). Other studies used quantitative mass spectrometry or SDS-PAGE and western blotting to measure changes in the relative abundance of proteins in the proteome of aging model systems (Depuydt et al, 2013Kirstein-Miles et al, 2013;Walther et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The relatively short lifespan of C. elegans makes it a convenient aging model system, and many of the preceding observations regarding changes in protein synthesis with aging come from work using this model organism (Depuydt et al, 2013Hansen et al, 2007;Kirstein-Miles et al, 2013;Pan et al, 2007;Stout et al, 2013;Walther et al, 2015). One of the best-characterized strains is the long-lived insulin receptor daf-2 mutant, which is generally found to have decreased protein synthesis or translation activity (Depuydt et al, 2013Hansen et al, 2007;Pan et al, 2007;Stout et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the dawn of the omics era, transcriptomic (McElwee et al, 2003;Murphy et al, 2003;McElwee et al, 2004;Halaschek-Wiener et al, 2005), proteomic (Dong et al, 2007;Jones et al, 2010;Depuydt et al, 2013Depuydt et al, , 2014Stout et al, 2013;Walther et al, 2015) and metabolomic (Fuchs et al, 2010) studies showed that IIS mutants undergo massive changes in gene expression and shifts in metabolic networks. DAF-16 targets were also determined by analysing DNA binding sites of this transcription factor with DamID and ChIP (Oh et al, 2006;Schuster et al, 2010).…”
Section: The Foxo/daf-16 Lifespan Programmentioning
confidence: 99%
“…Quantitative proteomics data showed a clear decrease in ribosomal subunits and translation factors in daf-2 mutants suggesting a decrease in protein synthesis rates in these worms (Depuydt et al, 2013;Stout et al, 2013). Active insulin and IGF pathways are known to support anabolic growth.…”
Section: Damage Clearance and Protein Turnovermentioning
confidence: 99%